The Timeless Quest for Truth in a World of Doubt: Re-Examining Modes of Proof in the Medieval Era - Amon, Isaac (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
This article presents a brief overview of historical methods of legal proof prior to and soon after the Norman Conquest of England in October 1066. Through an examination of the rituals of compurgation and the ordeal, which were techniques designed to discover truth prior to the establishment of the inquisition in medieval Europe and the common law jury trial in England, the human quest for intellectual conviction has been indelibly with us since the days of antiquity. And, whichever method to ascertain truth is ultimately utilized – compurgation or ordeal, inquisition or cross-examination, trial by judge or by jury – the law’s enduring search for certainty amidst a world of doubt owes much to the history and times of William the Conqueror.